Introduction of Broadcasting Technology to Support the Promotion of Local Products - Sugiarto, Yusron (Journal of Innovation and Applied Technology, 2024)
In today's digital age, broadcasting plays a crucial role in showcasing the potential of rural areas. It serves as a platform for educating the public, fostering community engagement, and establishing partnerships. This initiative was implemented in Kalipuro Village, Banyuwangi Regency, chosen for its promising prospects in tourism, culture, industry, agriculture, and livestock. The main objectives of this initiative are to introduce the village's potential, educate the community, encourage youth participation, foster partnerships, and promote entrepreneurship and the local economy. The activities involved in this initiative include conducting location surveys and obtaining permits, preparing and executing field activities, organizing Forum Group Discussions (FGD) and providing Technical Guidance, developing and producing broadcasting media, setting up Mini Broadcast Centers, providing training and mentoring for broadcast production, and monitoring and evaluating programs. This resulted in potential mapping, strategic solutions, and technical implementation plans.